Penerapan Relaksasi Otot Progresif Untuk Menurunkan Tekanan Darah pada Penderita Hipertensi di Bangsal Anggrek 2 RSUD Dr Soediran Mangun Sumarso Wonogiri - Siti Muyasaroh; Fida’ Husain; Sumardi, Sumardi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
The prevalence of hypertension continues to increase from year to year. Hypertension sufferers in Indonesia amounted to 34.1% in 2018. The RI Central Bureau of Statistics stated that in 2018 the prevalence of hypertension sufferers in Central Java was at the third level with a total of 37.6%. Uncontrolled hypertension can lead to complications of other diseases such as coronary heart disease, infarction, stroke, congestive heart failure, kidney failure and even death. So the need for patient compliance in preventing complications. The aim of applying progressive muscle relaxation to lower blood pressure in hypertensive patients at the Orchid Ward 2 RSUD dr Sodiran Mangun Sumarso Wonogiri. The research method used is descriptive case study. This study describes the results of an analysis of the application of progressive muscle relaxation in two patients with hypertension with certain criteria to reduce blood pressure in hypertensive patients in the Orchid Ward 2 RSUD Dr Soediran Mangun Soemarso Wonogiri. The application of progressive muscle relaxation can affect the decrease in blood pressure in hypertensive patients at the Anggrek Ward 2 RSUD Dr Soediran Mangun Soemarso Wonogiri. It can be concluded that progressive muscle relaxation has an effect on reducing blood pressure in hypertensive patients in the Anggrek 2 ward at Soediran Mangun Soemarso Hospital Wonogiri. Suggestions for hospitals, education, nurses, patients and families of this study can be a basic reference in managing blood pressure in hypertensive patients.